Enhanced elevations of hypo-osmotic shock-induced cytosolic and nucleic calcium concentrations in tobacco cells by pretreatment with dimethyl sulfoxide. Issue 2 (1st February 2019) - Nguyen, Hieu T. H.; Bouteau, François; Mazars, Christian; Kuse, Masaki; Kawano, Tomonori
ABSTRACT: Dimethyl sulfoxide (DMSO) is a dipolar aprotic solvent widely used in biological assays. Here, we observed that DMSO enhanced the hypo-osmotically induced increases in the concentration of Ca 2+ in cytosolic and nucleic compartments in the transgenic cell-lines of tobacco (BY-2) expressing aequorin.